Kajian terhadap Perkawinan Sedarah dalam Ritual Adat Tue Pose di Desa Serinuho, Kecamatan Titehena, Kabupaten Flores Timur - Paulina Oa Padu Hayon; Gisela Nuwa; Abdullah Muis kasim (Jurnal Ragam Pengabdian, 2026)
Consanguineous marriage is a marriage that is contrary to the laws of the Republic of Indonesia, religious law, and customary law. Customary law on marriage in the community in Serinuho village does not allow someone to enter into a marriage relationship with someone who is still a blood relative. However, in reality, consanguineous marriages still often occur in the Serinuho village community. The occurrence of consanguineous marriages is due to the lack of public knowledge about the applicable customary law, where this consanguineous marriage can cause challenges in family life such as having deformed offspring and other bad things. The purpose of this study was to determine the reasons for consanguineous marriages in Serinuho village and to determine the traditional rituals carried out in the process of consanguineous marriages in Serinuho village. This study uses a descriptive qualitative method. Primary data sources are, Customary Leaders, Customary Elders, Society, and Actors of Consanguineous Marriages. and Secondary data sources are Journals and Articles. Data collection techniques used are observation, interviews, and documentation. Data analysis by collecting data, reducing data, presenting data, and finally drawing conclusions. The results of the study showed that: Consanguineous marriages carried out in Serinuho Village which still have close blood relations and kinship in the same tribe, this occurs because there are still marriages obtained by mutual consent, marriages that do not meet the customary rules of the three furnaces, and the lack of participation of young people in traditional ceremonies involving the extended family. from this incestuous marriage conflict a traditional ritual emerged, namely Tue Pose. This Tue Pose ritual is a ritual for straightening the traditional tribe of a girl from her original tribe to another traditional tribe that is legitimate and correct to be married by a male tribe.